PENERAPAN PEMBELAJARAN MENDALAM (DEEP LEARNING) DI SEKOLAH DASAR: STUDI LITERATUR - Abd Haris Zainuddin; Muhammad Nazimuddin Al Kamil; Rahayu Japar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to systematically examine the implementation of deep learning in elementary schools through a Systematic Literature Review (SLR) approach. The review focuses on five main aspects: the concepts and principles of deep learning, supporting instructional models and strategies, the role of teachers in pedagogical practice, the impacts of deep learning along with the assessment approaches employed, and implementation challenges as well as existing research gaps. The literature search was conducted using reputable academic databases, with publications limited to the last five years to ensure the relevance of findings to contemporary curriculum developments and educational practices. The data were analyzed using thematic analysis to identify key patterns and trends across the reviewed studies. The findings indicate that deep learning in elementary education is consistently understood as a pedagogical approach that emphasizes conceptual understanding, active student engagement, meaningful reflection, and the development of higher-order thinking skills. The depth of learning is found to be more strongly influenced by teachers’ pedagogical design, the quality of learning interactions, and the use of continuous formative assessment than by the adoption of specific instructional models or technologies. However, most existing studies remain short-term in nature and are predominantly conducted in urban school contexts. Therefore, further longitudinal and context-sensitive research, particularly in rural areas, is needed to strengthen the sustainability of deep learning implementation in elementary schools.